Elevated Central Venous to Arterial CO2 Difference Is Not Associated With Poor Clinical Outcomes After Cardiac Surgery With Cardiopulmonary Bypass in Children. Issue 9 (September 2017) - Akamatsu, Takaaki; Inata, Yu; Tachibana, Kazuya; Hatachi, Takeshi; Takeuchi, Muneyuki
Abstract : Objective: To investigate whether elevated central venous to arterial CO2 difference is associated with delayed extubation and prolonged ICU stay in children after cardiac surgery with cardiopulmonary bypass. Design: Retrospective review of medical records. Setting: PICU in a tertiary children's hospital. Patients: Pediatric patients younger than 18 years old who underwent cardiac surgery with cardiopulmonary bypass between January 2014 and December 2014. Interventions: None. Measurements and Main Results: In total, 114 patients were included in this study. On ICU admission, blood samples were obtained simultaneously from an arterial line and a central venous line. There were no strong correlations between central venous to arterial CO2 difference (median, 11.1 [8.4–13] mm Hg) and other commonly used variables for the assessment of oxygen delivery including arteriovenous oxyhemoglobin saturation difference ( R 2 = 0.16) and blood lactate concentration ( R 2 = 0.02). When the patients were divided into two groups, based on the CO2 difference, the high group (difference ≥ 6 mm Hg; n = 103 [90%]) and the low group (difference < 6 mm Hg; n = 11 [10%]) showed no difference in the time to extubation (6 vs 5 hr, respectively; p = 0.80) or in the time to discharge from ICU (4 vs 5 d, respectively; p = 0.49). There was no mortality within 30 days of surgery. Conclusions: Elevation of central venous to arterial CO2 difference on ICU admission in children after cardiac surgery with cardiopulmonary bypass does not appear to be associated with delayed extubation or prolonged ICU stay.